Case report: A case of new mutation in SERPINC1 leading to thrombotic microangiopathy - Li, Bing; Zhang, Xiaohui; Lv, Hailin; Yang, Xiaoqing; Gao, Yanxia; Hu, Zhao; Ma, Chengjun (Frontiers in Genetics, 2023)
Hereditary antithrombin-III deficiency can significantly increase the risk for thrombosis, which is common in limb deep vein and pulmonary cases. However, thrombotic microangiopathy (TMA) caused by hereditary antithrombin deficiency is rare.We reported the case of a 32-year-old Chinese female patient with TMA with renal injury caused by decreased antithrombin-III activity due to a new mutation (chr1-173884049 c.50A>G) in SERPINC1, which encodes antithrombin-III. In this case, the patient had no history of relevant drug use, diabetes, or monoclonal plasma cells in the bone marrow puncture. Consequently, TMA of the kidney was considered secondary to hereditary antithrombin-III deficiency. Gene detection was the only clue that led us to suspect that TMA was caused by hereditary antithrombin deficiency.Our findings indicated that for patients with repeated findings of antithrombin-III activity less than 50%, the possibility of antithrombin-III deficiency and complete gene detection must be considered immediately after excluding the use of anticoagulants and lack of availability to facilitate early detection, diagnosis, and intervention.